If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 9 = -7 Reorder the terms: 9 + 9x = -7 Solving 9 + 9x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 9x = -7 + -9 Combine like terms: 9 + -9 = 0 0 + 9x = -7 + -9 9x = -7 + -9 Combine like terms: -7 + -9 = -16 9x = -16 Divide each side by '9'. x = -1.777777778 Simplifying x = -1.777777778
| 5e^3x=25 | | 3w^2-8w=35 | | -45x+10+2x=-4 | | c^2-2c+25= | | -8x+20y=40 | | (49x^2+25)(49x^2-25)= | | 8-8=3z-2 | | -28x-12-4x=3 | | -28=7w-49-4w | | X+25+x+2x=180 | | 4c^2-12cf+9f^2=0 | | 5x-3=180 | | -7y+2y+14=-11 | | 92-18= | | 23.6+x=16.25+9.6 | | (x-8)ln(x-8)=0 | | 4v^2-12vd+9d^2=0 | | 23x+3=180 | | 3x=3.75+3 | | 7x-56-5x=-38 | | 9+30x-25=-8 | | X-1.51=.74 | | -15y+16=86-29y | | 17w-9=8 | | x-4y-2z=0 | | 17w-9=18 | | (X^2-7x)=18 | | -6(7)=-42 | | (x+2)(x^2)=0 | | 2d+10=6d-6d | | 10.91*x^2-47.5*x+51.7=0 | | 15x-6=180 |